2005
DOI: 10.1111/j.1399-3054.2005.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

The family of Deg proteases in cyanobacteria and chloroplasts of higher plants

Abstract: The family of Deg proteases is present in nearly all organisms from bacteria to higher plants. This family consists of ATP‐independent serine endopeptidases with a catalytic domain of trypsin type and up to three PDZ domains, involved in protein–protein interactions. Sixteen deg genes (originally named degP1–16) were found in Arabidopsis thaliana, and the chloroplast location was predicted or experimentally proven for seven proteins. The cyanobacterium Synechocystis sp. PCC6803 contains three Deg homologues, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
90
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 45 publications
(81 reference statements)
0
90
0
Order By: Relevance
“…Photoinhibition on either the donor side or the acceptor side may trigger the damage and subsequent degradation of PSII proteins, particularly the D1 protein (Andersson and Aro, 2001;Huesgen et al, 2005). In acceptor-side photoinhibition, the primary cleavage of the D1 protein appears to occur in the stromal loop connecting the transmembrane helices D and E, based on the detection of 23-kD N-terminal and 10-kD C-terminal fragments in samples examined by various authors (Greenberg et al, 1987;Canovas and Barber, 1993;Shipton and Barber, 1994;Kanervo et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Photoinhibition on either the donor side or the acceptor side may trigger the damage and subsequent degradation of PSII proteins, particularly the D1 protein (Andersson and Aro, 2001;Huesgen et al, 2005). In acceptor-side photoinhibition, the primary cleavage of the D1 protein appears to occur in the stromal loop connecting the transmembrane helices D and E, based on the detection of 23-kD N-terminal and 10-kD C-terminal fragments in samples examined by various authors (Greenberg et al, 1987;Canovas and Barber, 1993;Shipton and Barber, 1994;Kanervo et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that all Arabidopsis thaliana Deg proteins were initially designated DegPs. However, because Deg1, Deg5, and Deg8 are more closely related to each other than to their E. coli homologs, it was recently suggested that they be renamed Degs (Huesgen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Chloroplasts contain at least one more distantly related homolog, Deg2, peripherally attached to the stromal side of the thylakoid membrane (Haussuhl et al, 2001). Ten other plant homologs are predicted to reside in chloroplasts, mitochondria, and maybe other cellular sites (Huesgen et al, 2005). It should be noted that all Arabidopsis thaliana Deg proteins were initially designated DegPs.…”
Section: Introductionmentioning
confidence: 99%
“…However, MEROPS database gives also the other name -AtDegP2. All AtDeg proteases were originally named as AtDegPX ones and then renamed just AtDegX [11]. It has been shown recently that AtDeg2 exhibits chaperone-like activity in vitro [14] yet no data exist with regard to how protease and chaperone activities are interlocked within a single AtDeg2 molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Sixteen genes coding for proteins orthologous to DegP, Q and S have been identified in the A. thaliana nuclear genome and designated AtDEG1-16 [11,12]. The genes code for proteins, which are targeted either to chloroplasts (AtDEG1, 2, 5, 7 and 8) or mitochondria (AtDEG10) or peroxisomes (AtDEG15).…”
Section: Introductionmentioning
confidence: 99%